Diabetic Ketoacidosis in COVID-19 Patients: Clinical Characteristics and Outcomes – A Retrospective Study in a Single Tertiary Care Hospital, Dubai, United Arab Emirates - Hana AL Sughaiyer; Abeer AL Haj; Samia Murad Ibrahim Abdulrahman (Dubai Diabetes and Endocrinology Journal)
Introduction: We aimed to evaluate the clinical characteristics of patients presenting with DKA and COVID-19 infection and describe the clinical outcomes compared to those without COVID-19. Methods: A retrospective study in a single tertiary care hospital in Dubai was conducted on patients admitted between 1st March 2020 and 30th July 2020 with a diagnosis of DKA with and without COVID-19 infection. Results: A total of 32 patients with DKA were identified. Eleven patients had a positive COVID-19 test and 21 patients were negative. The majority of DKA patients were males (84.4%). In the COVID-19 group, the mean age was 41.3 years old. Seven patients had preexisting diabetes (63.7%) and 4 patients (36.4%) had newly diagnosed diabetes. COVID-19 patients had a longer median length of hospital stay (7 days vs. 4 days; p = 0.278), shorter duration of DKA (16 h vs. 24 h; p = 0.043), and higher mortality (18.2% vs. 0%; p = 0.047). Conclusion: COVID-19 infection can precipitate DKA in patients with either newly diagnosed or preexisting diabetes. DKA patients with COVID-19 infection had higher mortality compared to those without COVID-19. This should urge physicians to be more vigilant in assessing the glycemic status of patients presenting with COVID-19 infection.